iPemphigus foliaceous in a dog associated with asymptomatic inflammation of the liver and heart - PAPADOGIANNAKIS, E.; FRAGIA, K.; SPANAKOS, G.; KOUTINAS, A.; MATRALIS, D. (Journal of the Hellenic Veterinary Medical Society, 2017)
No abstract available